Kirchen und Glaeubige im postsowjetischen Osteuropa - Kasack, Wolfgang (Arbeiten und Texte zur Slavistik, 1996)
The volume goes back to a symposium of the Department of Religious Studies of the German Society for Eastern European Studies, which took place in November 1995 in Bonn and was dedicated to the current changes of the Christian churches and the new situation for the faithful in Eastern Europe. Contributions to theology, history and literature have been incorporated in revised form.